#### Answer

$f'(x) = e^{-x}(2x-3)$

#### Work Step by Step

$f(x) = (1-2x)(e^{-x})$
Using Product Rule:
$f'(x) = (-2)(e^{-x}) + (1-2x)(-e^{-x}) = e^{-x}(2x-3)$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$f'(x) = e^{-x}(2x-3)$

$f(x) = (1-2x)(e^{-x})$
Using Product Rule:
$f'(x) = (-2)(e^{-x}) + (1-2x)(-e^{-x}) = e^{-x}(2x-3)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.